2020
DOI: 10.1002/adhm.201901656
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiology Assays with Applications in Cardiomyocyte Biology and Cardiotoxicity

Abstract: Cardiomyocytes are the motor units that drive the contraction and relaxation of the heart. Traditionally, testing of drugs for cardiotoxic effects has relied on primary cardiomyocytes from animal models and focused on short‐term, electrophysiological, and arrhythmogenic effects. However, primary cardiomyocytes present challenges arising from their limited viability in culture, and tissue from animal models suffers from a mismatch in their physiology to that of human heart muscle. Human‐induced pluripotent stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 191 publications
0
32
0
3
Order By: Relevance
“…Multiple approaches have been reported to assess contractile function in iPSC-CMs, including motion assessment in 2D monolayers, 3D microtissue approaches, and the single cell micropatterning approach, as recently reviewed. (Blair and Pruitt, 2020) While 2D monolayer motion analysis is simple, disorganized myofibrillar organization limits accuracy and reproducibility. In contrast, Ribeiro et al demonstrated that the single iPSC-CM micropatterning approach has advantages of single cell precision and control over cell shape, which was shown to exert a large influence on contractile function.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple approaches have been reported to assess contractile function in iPSC-CMs, including motion assessment in 2D monolayers, 3D microtissue approaches, and the single cell micropatterning approach, as recently reviewed. (Blair and Pruitt, 2020) While 2D monolayer motion analysis is simple, disorganized myofibrillar organization limits accuracy and reproducibility. In contrast, Ribeiro et al demonstrated that the single iPSC-CM micropatterning approach has advantages of single cell precision and control over cell shape, which was shown to exert a large influence on contractile function.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the heterogeneous structural color microfibers could realize single‐cell‐level sensing with a sensitivity at the µN scale, similar to the microfiber‐based cardiac force detection. [ 51 ] Although a sensitivity gap with single‐cell detection methods, such as AFM (reach to 10 pN), [ 8 ] TFM (around nN) [ 11 ] and elastomeric microarrays (around nN), [ 13 ] still exists, the sensitivity of this heterogeneous microfiber could be further improved by series of optimizations. The unique feature of the force–optical visible transformation of these microfibers would greatly simplify the complexity and reduce the expenditure of the whole detection system.…”
Section: Resultsmentioning
confidence: 99%
“…[ 1–3 ] As the abnormality of the cellular mechanical forces was usually corresponding to dysregulated function and diseased anatomical states, these forces have been gradually regarded as an element for disease evaluation. [ 4–7 ] To effectively measure the cellular level mechanical force, various force sensing techniques have been proposed and developed, such as atomic force microscope, [ 8,9 ] traction force microscopy, [ 10,11 ] elastomeric micropost array assays, [ 12,13 ] , etc. [ 14–18 ] Although with great advantages in biomechanical process and subcellular structure observation, most of these technologies depend on sophisticated equipment and cumbersome analog computation, which is expense‐demanding and time‐consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiomyocytes derived from induced pluripotent stem cells (iPSC-CMs) have high potential as a model system for investigating causal mechanisms in cardiomyopathies and for pharmaceutical testing. Multiple approaches have been reported to assess contractile function in iPSC-CMs, including motion assessment in two-dimensional (2D) monolayers, three-dimensional (3D) microtissue approaches, and the single-cell micropatterning approach, as recently reviewed ( Blair and Pruitt, 2020 ). While 2D monolayer motion analysis is simple, disorganized myofibrillar organization limits accuracy and reproducibility.…”
Section: Introductionmentioning
confidence: 99%